45th AIAA/ASME/SAE/ASEE Joint Propulsion Conference &Amp;amp; Exhibit 2009
DOI: 10.2514/6.2009-5282
|View full text |Cite
|
Sign up to set email alerts
|

In-Space Propulsion High Voltage Hall Accelerator Development Project Overview

Abstract: NASA's Science Mission Directorate In-Space Propulsion Technology Project is funding the development of a high specific impulse long life Hall thruster. The goal of the high voltage Hall accelerator (HiVHAc) project is to develop a flight-like, engineering model (EM) Hall thruster that can meet future NASA science mission requirements. These requirements are met by a thruster that operates over an input power range from 0.3 to 3.5 kW, attains specific impulses from 1,000 to 2,700 seconds, and processes at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…1 Indeed, the advanced magnetic field topologies that are being used in many state-of-the-art (SOA) Hall thrusters today have led to improvements both in performance and wear. 2,3,4,5,6 However, channel erosion has not been eliminated or reduced sufficiently to retire the risk for deep-space science missions.…”
Section: Introductionmentioning
confidence: 99%
“…1 Indeed, the advanced magnetic field topologies that are being used in many state-of-the-art (SOA) Hall thrusters today have led to improvements both in performance and wear. 2,3,4,5,6 However, channel erosion has not been eliminated or reduced sufficiently to retire the risk for deep-space science missions.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, insights gained from the temperature measurements will result in a better understanding of the power deposition into the thruster's internal components at various power levels. [18,19,20] In general, the thermal characterization results confirmed that the design changes incorporated in the EDU 2 thruster alleviated the elevated inner electromagnet temperatures that were encountered during EDU 1 thruster tests. Peak inner electromagnet temperatures of approximately 480 °C were measured at 4.2 kW.…”
Section: Thermal Characterization Testsmentioning
confidence: 55%
“…The Hall thruster modeled in the present work is NASA's High-Voltage Hall Accelerator, or HiVHAc. [15][16][17][18] The HiVHAc project is jointly conducted by NASA Glenn Research Center and Aerojet Rocketdyne with the goal of producing a long-life, high-specific-impulse Hall thruster for Discovery-class missions. The current engineering development unit (EDU2), has demonstrated operation at discharge voltages up to 650 V and discharge powers in excess of 4 kW.…”
Section: B Hall Thruster Simulation Setupmentioning
confidence: 99%